Do lean manufacturing practices have negative impact on job satisfaction? - Khaw, Sui Minh; Zailani, Suhaiza; Iranmanesh, Mohammad; Heidari, Shima (Emerald, 2019)
Purpose: Due to the increasing trend of global competitiveness, lean manufacturing has received much attention in the international literature. Although previous studies have indicated the positive effects of lean manufacturing on the performance of the manufacturing firms, the impact of lean practices on two aspects of “job”, namely, characteristics and satisfaction, as of yet remains unclear. As a result, this study aims to evaluate job characteristics to understand the effects of lean manufacturing on job satisfaction. Design/methodology/approach: Data from a survey of 206 employees in lean manufacturing companies were gathered and analysed using the partial least squares technique. Findings: The results indicate that customer relationship, human resources and product design practices had positive indirect effects on job satisfaction through job characteristics, whereas, process and equipment practices had a negative indirect effect. Practical implications: The findings of the study will be useful for the companies that implement lean manufacturing practices. Companies could either adjust their lean initiatives or make a trade-off amongst job characteristics. Originality/value: This study contributes to the advancement of knowledge on the effects of lean manufacturing practices on job satisfaction through job characteristics. © 2018, Emerald Publishing Limited.